Two-dimensional extended warranty strategy including maintenance level and purchase time: A win-win perspective. (March 2020) - He, Zhen; Wang, Dongfan; He, Shuguang; Zhang, Yiwen; Dai, Anshu
Highlights: Expanded the application of Generalised Polya Process in warranty decision making. Preventive maintenance, purchase time of EW and usage diversity are considered. A real case is presented to illustrate the application of the proposed model. Give suggestions on extended warranty purchase decisions from win-win perspective. Abstract: In practice, consumers need to decide whether and when to purchase extended warranty (EW), and there are many factors that influence this decision, such as product reliability and preventive maintenance (PM) conditions, etc. Under the consideration of consumer PM options, purchase time of EW and consumer usage rate diversity, this research first determines the product failure processes based on Generalised Polya Process (GPP) failure mode. Moreover, considering the impact of consumers purchasing decision of EW on warranty costs, we establish warranty cost models based on the product failure processes. Finally, given the warranty cost model, win-win EW price decision models are proposed in the product life cycle. A real case from a leading automobile manufacturer of China is presented to illustrate the application of the proposed model. The isoline of win-win regions and win-win EW intervals are obtained. Also, two management recommendations are given to help manufacturers make relevant decisions.